2015
DOI: 10.1177/1934578x1501000912
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Antibacterial Activity of Extracts and Alkaloids of Selected Amaryllidaceae Species

Abstract: Alkaloidal extracts of six selected species of Amaryllidaceae were studied with respect to their antibacterial and anti-yeast activity and their alkaloidal fingerprint. Twenty-five alkaloids were determined by GC/MS, and sixteen of them identified from their mass spectra, retention times and retention indexes. In the antimicrobial assay, Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus were used, along with isolates of the human pathogenic yeasts Candida albicans, C. glabrata, C. dublinie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(60 citation statements)
references
References 7 publications
(1 reference statement)
0
60
0
Order By: Relevance
“…The main metabolite of lycorine degradation, ungeremine, and carbamate substitution at C-1 and C-2 of lycorine had stronger antibacterial activity toward fish bacterial pathogen Flavobacterium columnare isolates than lycorine itself [37,38]. Lycorine though shows almost no inhibitory activity against Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus [39], a recent study by Bendaif and colleagues demonstrated the anti-bactericidal effect of lycorine in several bacterial strains, suggesting a preferential antibiotic property of lycorine [40].…”
Section: Antibacterial Effectsmentioning
confidence: 97%
See 1 more Smart Citation
“…The main metabolite of lycorine degradation, ungeremine, and carbamate substitution at C-1 and C-2 of lycorine had stronger antibacterial activity toward fish bacterial pathogen Flavobacterium columnare isolates than lycorine itself [37,38]. Lycorine though shows almost no inhibitory activity against Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus [39], a recent study by Bendaif and colleagues demonstrated the anti-bactericidal effect of lycorine in several bacterial strains, suggesting a preferential antibiotic property of lycorine [40].…”
Section: Antibacterial Effectsmentioning
confidence: 97%
“…The promising and varied degree of anti-yeast properties of lycorine were detected in several strains of Saccharomyces cerevisiae [48], Cryptococcus laurentii [49] and Candida albicans [39]. The anti-parasitic effects of lycorine depend on the mitochondrial genes, and strains that lack the mitochondrial genome were found to be resistant to high concentrations of this compound [50][51][52][53][54].…”
Section: Anti-parasitic Propertiesmentioning
confidence: 99%
“…Seven representatives of the lycorane group were identified in studies of fungal pathogenesis, including lycorine ( 5 ), amarbellisine ( 6 ), galanthine ( 7 ), 9‐ O ‐demethylgalanthine ( 8 ), caranine ( 9 ), acetylcaranine ( 10 ), and pseudolycorine ( 11 ) (Scheme ). As also seen for the majority of biological screens of lycorane alkaloids (Bastida et al, ), the parent compound lycorine was the most studied alkaloid of the group in assays of fungal pathogenesis (Bonvicini et al, ; De Leo, Dalessandro, De Santis, & Arrigoni, ; Evidente et al, ; Jimenez et al, ; Ločárek et al, ; Onofri, Barreca, & Garuccio, ). In contrast to its lack of activity against most bacterial pathogens (Nair, Wilhelm, Bonnet, & Van Staden, ), lycorine ( 5 ) was notably more active in the six fungal cultures against which it has been screened.…”
Section: Antifungal Activities Of Isolatesmentioning
confidence: 86%
“…Minimum quantity (μg) required for activity; na, not active. Standards: Nystatin MICs 4, 8, and 8 μg/ml against C. albicans , C. parapsilosis , and C. neoformans , respectively (Pagning et al, ); Chlorotrimazole MIC not given against C. albicans (Evidente et al, ); Amphotericin B MIC 0.6 μg/ml against C. albicans (Bonvicini et al, ); Tioconazole MICs 4, 0.03, 0.125, and 0.03 μg/ml against C. albicans , C. dubliniensis , C. glabrata , and L. elongisporus , respectively (Ločárek et al, ); Ketoconazole MIC not given against S. cerevisiae (Castilhos et al, ); Ketoconazole MICs 0.87, 0.92, and 1.26 μg/ml against A. niger , C. albicans , and T. rubrum , respectively (Wu et al, ).…”
Section: Antifungal Activities Of Isolatesmentioning
confidence: 99%
“…Among these alkaloids, galanthamine is a long-acting, reversible, selective and competitive acetylcholinesterase inhibitor used clinically for the treatment of mild to moderate Alzheimer's disease (Heinrich and Teoh 2004). Another important metabolite -lycorine (the main phenanthridine Amaryllidaceae alkaloid) -has been proven to possess several biological activities such as antiinflammatory (Saltan Çitoğlu et al 2012), antiviral (Li et al 2005;Oluyemisi et al 2015), antimalarial (Şener et al 2003(Şener et al ), antifungal (Shen et al 2014Locarek et al 2015), antiparasitic (Giordani et al 2011;Giordani et al 2012) and hepatoprotective (Ilavenil et al 2012) effects. In particular, lycorine showed significant cytotoxic activity over different cancer cell lines due to its chemical structure (Nair and van Staden 2014;Doskočil et al 2015;Nair et al 2016) as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%